The Influence of Education Management on Learning Motivation in Early Childhood - Dwi Septi Anjas Wulan; Muhammad Syaleh (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2023)
Learning motivation in early childhood is an important factor in achieving educational goals. This study aims to analyze the effect of education management on learning motivation in early childhood. The research methodology used in this study is a literature study. A literature study is a research approach carried out by collecting, reviewing, analyzing, and synthesizing literature or written sources that are relevant to the research topic used as the object of research. The results of this study show that the influence of education management on learning motivation in early childhood is very important. Factors that influence learning motivation in early childhood include internal factors, such as interest and talent, and external factors, such as the learning environment and learning methods. With good education management, teachers and education managers can create a conducive learning environment and motivate children to learn. Some strategies that can be used include interactive and fun learning methods, a safe and comfortable learning environment, and positive rewards and feedback.